Evaluación de la integridad de la mucosa intestinal en pollos de carne alimentados con diferentes niveles de botón de oro (Tithonia diversifolia) - Núñez Cofre, Katherine Michelle (2023)
Feeding fiber to broilers provides the functional nutrients necessary for the bird to be healthy, to have a good digestion at the small intestine level and to express its maximum production potential. In the present study, the inclusion of the buttercup plant (Tithonia diversifolia) in the diet of broilers during the growing period was evaluated in order to improve the integrity of the intestinal mucosa. For this purpose, 30 one-day-old broilers were randomly distributed in three treatments (0, 5 and 10 % of buttercup), the first served as control (without buttercup), the second included 5% buttercup and the third included 10% buttercup. The diets were formulated according to the recommendations of the Cobb 500 genetic line, and were fed ad libitum. The animals were sacrificed at 24 days of age. Samples were taken from the intestine portion (jejunum) for the analysis of the study variables, the samples were processed and stained with the eosin and hematoxylin technique. The animals that consumed the diet with 10% buttercup obtained a higher ratio (villus length/crypt depth P= 0.01). It is concluded that the inclusion of high levels of buttercup in feed rations for growing broilers favors the development of intestinal mucosal integrity in the growing phase. Keywords: Buttercup, intestinal mucosa, villi, crypt depth.